Continuity and Change in Orthodox Christianity in Contemporary Russia: Enduring Legacies and New Developments in the Making - Koellner, Tobias (Religions, 2021)
Drawing on ethnographic fieldwork in two cities of European Russia, this article analyzes continuity and changes in Orthodox Christianity. In so doing, we emphasize property restitution, the renovation of sacred sites, and the importance of religious education in public schools and parishes. Based on that ethnographic material, we address three related research topics. First, we would like to discuss the importance of Orthodox Christianity for contemporary Russia. Second, we aim to show that an understanding of the Russian Orthodox Church as a national church underscores the local and internal differences as well as the complexities of everyday interactions. Finally, we address the notion of postsocialism and discuss its limits and potentials for the analysis of contemporary Russia.